The preparedness of physical education graduates to plan and implement physical activity programs for seniors - Kartashova V.N.; Puzatykh A.N.; Shcherbatykh L.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to ascertain the framework of the preparedness of physical education graduates to engage with the elderly and to ascertain the educational potential for its development in the context of foreign language instruction. Methods and structure of the study. The theoretical framework for this research was grounded in the principles of competence-based, gerontological, integrative, activity-oriented, and systematic approaches to the training of bachelors in the field of 49.03.01 «Physical Culture». The research was conducted at the Institute of Physical Education, Sports, and Life Safety at I.A. Bunin Yelets State University from 2022 to 2024, focusing on foreign language classes for first- and second-year students. A total of 52 students participated in the experiment. Results and conclusions. The framework for the preparedness of future physical education bachelors to work with the elderly is outlined: a combination of motivational and value-based, theoretical and practical readiness, encompassing operational, organizational, methodological, and reflective aspects. The content-technological framework for this process has been established, and the content-technological foundation for its development in the context of foreign language education has been established.